Constitutive Activation of Leucine-Rich Repeat Receptor Kinase Signaling Pathways by BAK1-INTERACTING RECEPTOR-LIKE KINASE3 Chimera. Issue 10 (13th August 2020) - Hohmann, Ulrich; Ramakrishna, Priya; Wang, Kai; Lorenzo-Orts, Laura; Nicolet, Joel; Henschen, Agnes; Barberon, Marie; Bayer, Martin; Hothorn, Michael
Abstract : A protein engineering approach allows the constitutive activation of LRR membrane receptor kinase signaling pathways in plants. Abstract: Receptor kinases with extracellular leucine-rich repeat domains (LRR-RKs) form the largest group of membrane signaling proteins in plants. LRR-RKs can sense small molecule, peptide, or protein ligands and may be activated by ligand-induced interaction with a shape complementary SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE (SERK) coreceptor kinase. We have previously shown that SERKs can also form constitutive, ligand-independent complexes with the LRR ectodomains of BAK1-INTERACTING RECEPTOR-LIKE KINASE3 (BIR3) receptor pseudokinases, negative regulators of LRR-RK signaling. Here, we report that receptor chimera in which the extracellular LRR domain of BIR3 is fused to the cytoplasmic kinase domains of the SERK-dependent LRR-RKs BRASSINOSTEROID INSENSITIVE1, HAESA and ERECTA form tight complexes with endogenous SERK coreceptors in the absence of ligand stimulus. Expression of these chimeras under the control of the endogenous promoter of the respective LRR-RK leads to strong gain-of-function brassinosteroid, floral abscission, and stomatal patterning phenotypes, respectively. Importantly, a BIR3-GASSHO1 (GSO1)/SCHENGEN3 (SGN3) chimera can partially complement sgn3 Casparian strip formation phenotypes, suggesting that SERK proteins also mediate GSO1/SGN3 receptor activation. Collectively, our protein engineering approach may be used to elucidate the physiological functions of orphan LRR-RKs and to identify their receptor activation mechanism in single transgenic lines.